KONSEP ETIKA KONSUMEN MUSLIM: PERSPEKTIF SYARIAH DAN IMPLEMENTASI DALAM PERILAKU KONSUMSI KONTEMPORER - Sari, Winda Novita; Mahyarni, Mahyarni; Hardiansyah, Kiki (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to examine Global Islamic economic growth and increasing religious awareness among Muslims require a deep understanding of the concept of Muslim consumer ethics that governs purchasing decisions and consumption behavior. This study aims to analyze the concept of Muslim consumer ethics from a sharia perspective and its implementation in the context of contemporary consumption. This study uses a qualitative approach with a literature analysis method. Data was collected from primary sources (the Qur'an and Hadith) and secondary sources (works by scholars, academic journals, and related books). The results of the research and discussion revealed that there are five main dimensions of Muslim consumer ethics: (1) awareness of halal-haram as a basic foundation, (2) the principle of wasatiyyah (moderation) in consumption, (3) social responsibility and environmental awareness, (4) spiritual orientation in consumption decisions, and (5) consideration of the public interest. The implementation of this concept in a contemporary context shows a complex dynamic between the ideals of sharia and practical realities. Muslim consumer ethics is a holistic value system that integrates spiritual, social, economic, and environmental dimensions. A comprehensive understanding of this concept is important for the development of products, marketing strategies, and policies that are in line with the needs of Muslim consumers.